(untitled) (Indian Journal of Arid Horticulture, 2016)
Genetic variability and character association analysis were estimated among sixteen genotypes of garlic for twelve characters comprised of bulb yield and its contributing characters in Randomized Block Design with three replications during Rabi-2014-15. Analysis of variance indicated presence of considerable variability for all the twelve characters. High GCV and PCV were observed for volume of bulb and weight of cloves. High estimates of heritability along with high genetic advance as per cent of mean was observed for volume of bulb and bulb yield indicating predominance of additive gene effects for these traits. The result from character association indicated that bulb yield had highly significant positive correlation with number of cloves per bulb, ascorbic acid and weight of cloves at both the levels.